2016
DOI: 10.4012/dmj.2014-269
|View full text |Cite
|
Sign up to set email alerts
|

Peel bond strength of soft lining materials with antifungal to a denture base acrylic resin

Abstract: The effect of the addition of nystatin, miconazole, ketoconazole, chlorhexidine, and itraconazole into the soft lining materials Softone and Trusoft on their peel bond strength to a denture base acrylic resin was evaluated. Specimens of soft lining materials (n=7) were made without (control) or with the incorporation of antifungals at their minimum inhibitory concentrations to the biofilm of C. albicans and bonded to the acrylic resin. Peel testing was performed after immersion in distilled water at 37ºC for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 65 publications
1
19
0
5
Order By: Relevance
“…Thus, all these mechanisms may have resulted in hardness increase of the soft lining materials with the 1.0% CHX addition, which leads to a decrease in their peel bond strength to the denture base resin. These findings corroborate with those of a recent study that demonstrated lower peel bond strength values for the Trusoft material after both the addition of CHX and itraconazole, regardless of the immersion time in distilled water 46) . Bertolini et al 18) suggest that the CHX incorporation did not lead to a clinically relevant change on the material.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, all these mechanisms may have resulted in hardness increase of the soft lining materials with the 1.0% CHX addition, which leads to a decrease in their peel bond strength to the denture base resin. These findings corroborate with those of a recent study that demonstrated lower peel bond strength values for the Trusoft material after both the addition of CHX and itraconazole, regardless of the immersion time in distilled water 46) . Bertolini et al 18) suggest that the CHX incorporation did not lead to a clinically relevant change on the material.…”
Section: Discussionsupporting
confidence: 92%
“…The pattern of CHX incorporation in the polymer results in fragility of the matrix and increases the porosity of the modified materials 44) . This porosity contribute to the CHX releasing, which is also favored by the higher solubility of its molecules in water (0.019 g/ mL) 46) . The addition of a substance such as a drug in a soft material might impair the plasticizers to penetrate in the polymeric chains and form a softened gel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of itraconazole, the MICs of drugs incorporated into temporary soft lining materials resulted in minimal changes in their peel bond strength to a denture base resin within 14 days 19 . After 14 days, the MICs of nystatin and ketoconazole in both materials and chlorhexidine in temporary resilient liner did not significantly influence their water sorption 10 .…”
mentioning
confidence: 99%